2015
DOI: 10.1111/joic.12231
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Geographic Miss (LGM) in Robotic Assisted Versus Manual Percutaneous Coronary Interventions

Abstract: Robotic-assisted PCI had significantly lower incidence of LGM compared to standard M-PCI. Reducing LGM potentially improves long-term clinical outcomes through reduction in MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 10 publications
1
24
0
Order By: Relevance
“…Further, the patients enrolled in the CORA-PCI trial were a diverse population; roughly 20% presented with acute coronary syndrome, and a substantial num- to M-PCI. 16 Longitudinal geographic miss is in turn associated with higher target lesion revascularization, 17 but no such benefit of robotic PCI was observed in the current study, likely due to it being underpowered to address such a difference.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Further, the patients enrolled in the CORA-PCI trial were a diverse population; roughly 20% presented with acute coronary syndrome, and a substantial num- to M-PCI. 16 Longitudinal geographic miss is in turn associated with higher target lesion revascularization, 17 but no such benefit of robotic PCI was observed in the current study, likely due to it being underpowered to address such a difference.…”
Section: Discussionmentioning
confidence: 54%
“…This long‐term follow‐up study of the original CORA‐PCI study provides confirmation that robotic PCI can be performed with high technical success and leads to short‐ and intermediate‐term outcomes which are comparable to the manual approach. Additional potential benefits unique to the robotic platform with its ability to perform micromanipulation of the balloon and stent delivery system in the coronary artery lower the incidence of longitudinal geographic miss when compared to M‐PCI . Longitudinal geographic miss is in turn associated with higher target lesion revascularization, but no such benefit of robotic PCI was observed in the current study, likely due to it being underpowered to address such a difference.…”
Section: Discussionmentioning
confidence: 71%
“…Similar numbers were shown when compared with objective robotic measurement . Although this information needs to be confirmed with prospective clinical data, by improving accuracy of lesion‐length assessment, robot‐assisted PCI hold the potential to reduce the risk of in‐stent restenosis and to improve patient outcomes . The impact of precise robotic lesion‐length measurement on stent length selection was studied in 60 consecutive patients by Campbell and colleagues.…”
Section: Possible Benefits Of Robot‐assisted Pcimentioning
confidence: 76%
“…Experience with these indications has shown that the key benefits of robotic assistance include increased procedural and technical accuracy, as well as reduced radiation dose during fluoroscopic procedures. It also offers the potential for truly ‘remote’ procedures 3 9–11…”
Section: Discussionmentioning
confidence: 99%